2016
DOI: 10.1016/j.spinee.2016.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Interpedicular height as a predictor of radicular pain in adult degenerative scoliosis

Abstract: Background Context Spine surgeons must correlate clinical presentation with radiographic findings in a patient-tailored approach. Despite the prevalence of adult degenerative scoliosis (ADS), there are few radiographic markers to predict presence of radiculopathy. Emerging data suggest that spondylolisthesis, obliquity, foraminal stenosis and curve concavity may be associated with radiculopathy in ADS. Purpose The purpose of this study was to determine if radicular pain in ADS is associated with reduced inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…To quantify foraminal height, the interpedicular distance was measured as previously described. 6 Index-level segmental lordosis (i.e., fused segment angle) was measured as the Cobb angle of the superior and inferior endplates at the TLIF level. Lumbar lordosis was measured as the lateral Cobb angle from the superior endplate of L-1 to the superior endplate of S-1.…”
Section: Radiographic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify foraminal height, the interpedicular distance was measured as previously described. 6 Index-level segmental lordosis (i.e., fused segment angle) was measured as the Cobb angle of the superior and inferior endplates at the TLIF level. Lumbar lordosis was measured as the lateral Cobb angle from the superior endplate of L-1 to the superior endplate of S-1.…”
Section: Radiographic Measurementsmentioning
confidence: 99%
“…A reduced or collapsed disc and foraminal height are associated with radicular symptoms, pain, and disability. 6,21 Few studies have evaluated the effects of MIS-TLIF on restoring disc height, and these studies have shown variable results. 8,10 For deformity surgery, restoring pelvic incidence-lumbar lordosis mismatch to less than 10° had a great impact on improving clinical performance scores.…”
mentioning
confidence: 99%
“…R 2 value of multiple linear regression analysis of LMA and CVA was very low in our study, which indicated that LMA could not accurately predict CVA. This might be explained by the effects of various factors on CVA [27].…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory curve at the lumbosacral region below the major curve is named the fractional curve; the nerve roots on the concave side of the fractional curve are the most frequent radicular pain generators in DLS patients [ 3 5 ]. The neurologic symptoms derived from the nerve root compression is strongly correlated with the decision to pursue surgical treatment; spine surgeons must include in surgical planning the symptomatic radicular levels that are related to the fractional curve instead of the major curve [ 6 ]. It has been recommended that all fractional curves greater than 15° must be corrected and included within the instrumentation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%